The foundations of mathematical development in Williams syndrome and Down syndrome. Issue 5 (20th April 2020) - Van Herwegen, Jo; Ranzato, Erica; Karmiloff‐Smith, Annette; Simms, Victoria
Abstract: Background: Studies in Down syndrome (DS) and Williams syndrome (WS) have suggested that mathematical abilities are impaired. However, it is unclear which domain‐general or domain‐specific abilities impact on mathematical development in these developmental disorders. Method: The current study examined the foundations of mathematical development across participants with WS ( n = 24) and DS ( n = 26) compared to typically developing (TD) children ( n = 26) in relation to domain‐general (i.e., general intelligence and visuospatial abilities) and domain‐specific abilities (non‐symbolic and symbolic number abilities). Results: Developmental trajectories showed that mathematical abilities were delayed in line with overall mental age in DS and WS. Whilst visuospatial abilities predicted performance for DS and TD participants, this was not the case for the WS group, instead Approximate Number Sense abilities predicted mathematical development. Conclusions: These findings suggest that those with DS and WS may benefit from different mathematical intervention programmes.